Meteorus consimilis - Stigenberg, Julia; Ronquist, Fredrik (Zenodo, 2011)
Meteorus consimilis (Nees von Esenbeck) Fig. 61, 62, 93 Perilitus consimilis Nees von Esenbeck, 1834:42. Syntypes ♂, Germany (destroyed). Perilitus brevipes Wesmael, 1835: 33 Lectotype ♂, Belgium: Brussels, coll. Wesmael (IRSNB, Brussels), Synonymized with albicornis Ruthe by Marshall, 1887:110. Meteorus albicornis Ruthe, 1862:34. lectotype ♀, Germany: Ruthe coll. (BMNH, London). Synonymized with consimilis by Thomson, 1895:2160 —examined Diagnosis : The only species that could be confused with this species is M. abdominator. A good separating character is the length of the malar space (almost two times basal breadth of mandible in M. consimilis , at most as long as basal breadth of mandible in M. abdominator . The length and shape of the ovipositor also differ between these species. The ovipositor of M. consimilis is thick, distinctly down-curved and short (equal in length to petiolar tergum), while M. abdominator has a thin and long (2.0–2.5 times length of petiolar tergum), and only slightly down-curved ovipositor. Studied material : ~ 60 specimens. Description : Size about 3–4mm. Antennae 32–33 articles; basally whitish. Head strongly contracted behind eyes. Ocelli large, OOL=1.5. Eyes small, not convergent. Malar space long, almost twice basal breadth of mandible. Clypeus strongly protuberant. Tentorial pits deep. Mandibles slender; strongly twisted. Precoxal sulcus deep, broad, reticulate-rugose. Propodeum strongly reticulate-rugose. Petiolar tergum short, wide, with distinct dorsal pits. Ovipositor short, at most equal in length to petiolar tergum; thick down-curved. Wings infumate and short. Colour dark. ♂ antennae 32–36 articles with no pale band. Distribution : Western Palearctic. Country records: Belgium; Croatia; Denmark; Finland; France; Germany; Hungary; Ireland; Latvia; Netherlands; Poland; Romania; Slovenia; Sweden; Switzerland; Turkey; Turkmenistan; Ukraine; United Kingdom; Yugoslavia. Biology : Meteorus consimilis is recorded as a parasitoid of Scolytus multistriatus (Yu et al. 2005). We found 58 specimens within the SMTP; they were caught in both deciduous and coniferous forests. Flying time is from middle of July to end of October. : Published as part of Stigenberg, Julia & Ronquist, Fredrik, 2011, Revision of the Western Palearctic Meteorini (Hymenoptera, Braconidae), with a molecular characterization of hidden Fennoscandian species diversity 3084, pp. 1-95 in Zootaxa 3084 (1) on page 51, DOI: 10.11646/zootaxa.3084.1.1, http://zenodo.org/record/5244448 : {"references": ["Nees von Esenbeck, (1834) Hymenopterorum Ichneumonibus affinium monographiae, genera Europaea et species illustrantes, 1, 320 pp Stuttgart, Tubingen, Cotta.", "Wesmael, C. (1835) Monographie des Braconides de Belgique. Nouveaux Memoires de l'Academie Royales des Science. Bruxelles, 9, 1 - 252.", "Marshall, T. A. (1887) Monograph of British Braconidae, Part II. Transactions of the Royal Entomological Society of London, 1887, 51 - 131.", "Ruthe, J. F. (1862) Deutsche Braconiden. Berlin Entomologishe Zeitschrift, 6, 1 - 58.", "Thomson, C. G (1895) Bidrag till Braconidernas kannedom. Opuscula Entomologica, 20, 2141 - 2339.", "Yu, D. S., Achterberg, C. van. (Braconidae) & Horstmann, K. (Ichneumonidae). 2005. World Ichneumonoidea 2004 - Taxonomy, Biology, Morphology and Distribution. DVD / CD. Taxapad. Vancouver, Canada. www. taxapad. com."]}